RNA-Based TWIST1 Inhibition via Dendrimer Complex to Reduce Breast Cancer Cell Metastasis. (11th February 2015) - Finlay, James; Roberts, Cai M.; Lowe, Gina; Loeza, Joana; Rossi, John J.; Glackin, Carlotta A.
Abstract : Breast cancer is the leading cause of cancer-related deaths among women in the United States, and survival rates are lower for patients with metastases and/or triple-negative breast cancer (TNBC; ER, PR, and Her2 negative). Understanding the mechanisms of cancer metastasis is therefore crucial to identify new therapeutic targets and develop novel treatments to improve patient outcomes. A potential target is the TWIST1 transcription factor, which is often overexpressed in aggressive breast cancers and is a master regulator of cellular migration through epithelial-mesenchymal transition (EMT). Here, we demonstrate an siRNA-based TWIST1 silencing approach with delivery using a modified poly(amidoamine) (PAMAM) dendrimer. Our results demonstrate that SUM1315 TNBC cells efficiently take up PAMAM-siRNA complexes, leading to significant knockdown of TWIST1 and EMT-related target genes. Knockdown lasts up to one week after transfection and leads to a reduction in migration and invasion, as determined by wound healing and transwell assays. Furthermore, we demonstrate that PAMAM dendrimers can deliver siRNA to xenograft orthotopic tumors and siRNA remains in the tumor for at least four hours after treatment. These results suggest that further development of dendrimer-based delivery of siRNA for TWIST1 silencing may lead to a valuable adjunctive therapy for patients with TNBC.